Comparative Analysis of the Autodock 4.2 and Autodock Vina Methods in Predicting Thiazolidinedione Interactions with PPARG Receptor - Reynaldi, Muhammad Andre; Faradilla, Aulia; Sari, Rafika; Riza, Hafrizal; Najini, Robby (Ad-Dawaa' Journal of Pharmaceutical Sciences, 2024)
Introduction: Molecular docking simulation is an in silico method that plays a role in drug discovery and analyzing drug interactions with receptors. The method using Autodock 4.2 and Autodock Vina is widely used in molecular docking simulations, especially for analyzing interactions that occur between ligands and receptors. Aims: This study was aims to compare the Autodock 4.2 and Autodock Vina methods in simulating the docking of thiazolidinedione against PPARG in terms of bond energy and type of interaction parameters. Methods: The method used in this research was molecular docking simulation using Autodock 4.2 and Autodock Vina. The two methods compared the interaction results and binding affinity scores in the thiazolidinedione group against PPARG. Result: The results of this study show that the interactions using the Autodock 4.2 and Autodock Vina methods have similar amino acids that are bound and the same active site. The binding affinity score also shows that the best are troglitazone, pioglitazone, native ligand and rosiglitazone. Conclusion: Based on the results of this study, it shows that molecular docking simulations using the Autodock 4.2 and Autodock Vina methods thiazolidinedione with PPARG have similar docking score patterns and almost the same types of interactions.